495=2x-(1-9x)+1

Simple and best practice solution for 495=2x-(1-9x)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 495=2x-(1-9x)+1 equation:


Simplifying
495 = 2x + -1(1 + -9x) + 1
495 = 2x + (1 * -1 + -9x * -1) + 1
495 = 2x + (-1 + 9x) + 1

Reorder the terms:
495 = -1 + 1 + 2x + 9x

Combine like terms: -1 + 1 = 0
495 = 0 + 2x + 9x
495 = 2x + 9x

Combine like terms: 2x + 9x = 11x
495 = 11x

Solving
495 = 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
495 + -11x = 11x + -11x

Combine like terms: 11x + -11x = 0
495 + -11x = 0

Add '-495' to each side of the equation.
495 + -495 + -11x = 0 + -495

Combine like terms: 495 + -495 = 0
0 + -11x = 0 + -495
-11x = 0 + -495

Combine like terms: 0 + -495 = -495
-11x = -495

Divide each side by '-11'.
x = 45

Simplifying
x = 45

See similar equations:

| 2(4)-5(2)=11 | | 8x^2+12x+18=0 | | 3x+32= | | 2(-7)-5(-5)=11 | | 5x-11=-29 | | 2(1)-5(-3)=11 | | 2x^3-6x^2+5x+15=0 | | 19+(1+0)= | | -2(-6+2s)-12=-3(6+6s)-5 | | 2(-9)-5(4)=11 | | -2x-(-2x-1)=7 | | 27=162-4 | | 23=6x+5 | | -9=-24-4 | | 6=-4x-30 | | 2(4x-3)-8=10+2x | | x-5.4=1 | | u^2+5u-36=0 | | 3x^7=7x | | 4m+m=180 | | x-5.7=3.6 | | -5k=-20 | | 16x+6=70 | | -10p+9p=14 | | 10=y-6 | | -2(x+7)=-14+2x | | -10=-14v+12v | | 5u^2-11u+2=0 | | -20=-4x-6x+10 | | 9x-8y=6 | | 3*4=3-5 | | -m+2q=-nq |

Equations solver categories